2015
DOI: 10.3109/02688697.2015.1071332
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of osteoblastoma associated to aneurysmal bone cyst of the spine. Case report

Abstract: Osteoblastoma is a rare bone tumour. It is occasionally associated with an aneurysmal bone cyst (ABC). Several treatment strategies can be adopted. We report a challenging case of an osteoblastoma associated with ABC of the lumbar spine in a 2-year-old boy. The pathogenesis and the critical management of the disease are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 3 publications
2
23
0
Order By: Relevance
“…Another, similar case was reported in an 11-year-old boy at the C4 level by Hu et al [9]. Pavanello et al [10] reported a similar pathology in the lumbar region (L2 level).…”
Section: Discussionsupporting
confidence: 48%
“…Another, similar case was reported in an 11-year-old boy at the C4 level by Hu et al [9]. Pavanello et al [10] reported a similar pathology in the lumbar region (L2 level).…”
Section: Discussionsupporting
confidence: 48%
“…Components of aneurysmal bone cysts are reported to be present in approximately 10%-15% of cases of osteoblastomas. 34,40,60,70,73,93 This finding may confound the final pathology findings. Osteoid osteoma transitioning to an osteoblastoma has been reported in the literature, although this not a common occurrence.…”
Section: Pathologymentioning
confidence: 81%
“…We found four cases of spinal osteoblastoma associated with secondary ABC in recently published studies. Three of these involved the cervical spine and one originated in lumbar vertebra [2][3][4][5] ( Table 1). Osteoblastoma combined with ABC in the spinal column has a high rate of recurrence if incomplete resection is done [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…We report a case with histologically proven osteoblastoma associated with secondary ABC arising from C4 cervical vertebra and eroding into adjacent vertebrae with a 2-year follow-up. To our knowledge, only four such cases have been documented in recent literature [2][3][4][5]. Early and correct diagnosis and complete removal can be a challenge given a protracted clinical presentation and cervical location that makes achieving a clean margin difficult.…”
Section: Introductionmentioning
confidence: 99%